Fertilizer-Nitrogen Use Efficiency Of Irrigated Wheat .1. Uptake Efficiency Of Preplant Versus Late-Season Application - Wuest, S.B.; Cassman, K.G. (Wiley, 1992)
The addition of N fertilizer late in the growing season to improve grain quality is a potential management option for production of irrigated hard red spring wheat (Triticum aestivum L.). This study compared the recovery of fertilizer N applied at planting with that of fertilizer N applied at anthesis, and evaluated the effects on soil N uptake. In a 2‐yr field study, N fertilizer rates of 120, 180, or 240 kg N ha−1 at planting and 0, 30, or 60 kg N ha−1 at anthesis were applied to ‘Yecora Rojo’ wheat. The experiment utilized a duplicate plot design such that for every N‐rate treatment there were two plots, one plot received 15N labeled fertilizer at planting, and the other received I5N labeled fertilizer at anthesis. The recovery of N applied at planting ranged from 30 to 55%, while that of N applied at anthesis ranged from 55 to 80%. The contribution of soil N (non‐fertilizer N) to total plant N was not affected by the N rate or timing of application. In another field study 120, 180, or 240 kg N ha−1 was applied at planting and 0 or 45 kg N ha−1 at anthesis the first year, and 85, 140, 195, and 250 kg N ha−1 applied at planting and 0, 25, 45, and 65 kg N ha−1 at anthesis the second year. A small dose (< 1 kg ha−1) of NH4‐15N was iqjected 5 cm below the soil surface to follow the effect of N application at anthesis on uptake of existing inorganic soil N. Fertilizer N at anthesis increased the amount of iqjected 15N taken up by the plants from 38 to 48% the first year, and from 49 to 61% the second year. In both studies, the amount of fertilizer N applied at anthesis had the greatest influence on postanthesis N uptake, which ranged from 17 to 77 kg N ha−1. Without supplemental N applied at anthesis, postanthesis N uptake only provided from 12 to 18% of the total grain N demand, and postanthesis N uptake was not increased by greater preplant N input levels. Likewise, extractable and mineralizable soil N at anthesis were not affected by preplant N treatments. These results indicate that a late N application can be efficiently taken up by plants, and does not decrease soil N uptake. To achieve acceptable grain protein levels for bread wheat in this. imgated cropping system, N should be supplied late in the season to improve N uptake during grain fill.